(untitled) (Journal of Global Humanities and Social Sciences, 2025)
With the deepening advancement of digital technologies and the full arrival of the digital era, corporate human resource management is undergoing unprecedented digital transformation. During this transition, organizations face multiple challenges including strategic planning gaps, insufficient talent reserves, limitations in technology application, and organizational cultural barriers. These factors constrain the deep application of digital tools and the full exploitation of data value. Against this backdrop, this paper systematically explores innovative strategies for corporate HRM in the digital transformation era. It delves into the profound implications of connectivity and value within corporate HRM under digital transformation, providing theoretical guidance and practical pathways for enterprises to comprehensively advance the digital transformation of their human resource management.